Biogas Production from Water Hyacinth - Abdelwahab Sharaw, Adil; Basheer Ahmed , Tagwa; Anwar Zakaria, Zakaria (University of Khartoum Engineering Journal, 2022)
The main objective of this paper the conversion of the Water Hyacinth into a clean energy that can be exploited widely by a process of fermenting inside ferment devices. Three laboratory scale digesters were designed with different Water Hyacinth samples mixed with , water and Catalyst, the first model contains a green sample, the second sample was dried and the third was mixed green and dry with concentration of (34%, 18% and,24%), respectively. After ten days of fermentation the research showed that, the greater production of biogas was in the first digester (A). The second production was from digester (C), which contains the green and dry sample. The last one was digester (B) which contains the dry sample only with total volumes of (162509.71, 139273.12, 91540.35) cubic centimetres, respectively. The research shows that the green sample is the best in terms of the amount of gas produced.